Comparative Analysis of Vectorial Capacity Among Triatoma brasiliensis brasiliensis, Triatoma juazeirensis, and Their Experimental Hybrids - Nathália Cordeiro Correia; Carlos José de Carvalho Moreira; Fernanda Oliveira Firmino; Dayse da Silva Rocha; João Paulo Sales Oliveira-Correia; Cleber Galvão; Jane Costa (Microorganisms)
The existence of a natural hybridization zone of members of the Triatoma brasiliensis complex in Pernambuco, a Brazilian state with areas highly infested by Trypanosoma cruzi vectors, raised questions to be studied about the vectorial capacity of these hybrids. Recently, it was demonstrated that experimental hybrids of T. brasiliensis brasiliensis and Triatoma juazeirensis present vectorial competence superior to that of the parental species. The objective of the present study was to compare bionomic aspects related to the vectorial capacity of T. b. brasiliensis, T. juazeirensis, and their experimental hybrids. Feeding and defecation behavior patterns in fifth instar nymphs were comparatively analyzed between four groups, two parental and two hybrids, respectively: T. b. brasiliensis, T. juazeirensis, Hjb (♀ T. juazeirensis × ♂ T. b. brasiliensis), and Hbj (♀ T. b. brasiliensis × ♂ T. juazeirensis). Fifteen newly molted fifth instar nymphs from each of the mentioned groups were previously subjected to a period of fasting for 10 days and individually kept in identified bottles. In the experiment, the insects were placed in a jar containing a mouse immobilized in nylon mesh, in accordance with the guidelines of the animal ethics committee. The following variables were observed: 1-total number of feedings carried out; 2-time to start feeding; 3-duration of feeding and weight acquired; 4-defecations during feeding; 5-defecation within one minute after cessation of feeding; 6-defecation within ten minutes after cessation of feeding; 7-defecation behavior. Specimens from all groups demonstrated voracity, starting their meal immediately after contact with the mouse, and most of the insects defecated immediately after feeding, with 78% of the insects defecating within 30 s. The results obtained suggest that T. brasiliensis, T. juazeirensis, and their experimental hybrids presented bionomic characteristics compatible with the species considered good vectors in the literature. However, T. b. brasiliensis and T. juazeirensis demonstrated even more effective characteristics for T. cruzi transmission regarding their feeding and defecation patterns when compared to their hybrids.